HOLMIUM LASER: YAG LITHOTRIPSY IN URETERAL CALCULI MANAGEMENT - Sunaryo, Juhadi; Ali, Zulfikar; Danarto, H R (Indonesian Urological Association, 2016)
Objective: To know predictive factors for success of holmium laser: YAG lithotripsy in ureteral calculi management. Materials & Methods: This prospective cohort study was conducted in January 2013 to May 2015 at Kardinah Tegal Hospital Central Java. Patients diagnosed with proximal and distal stones were included. Pediatric, obesity, pregnancy, ureteral anomaly, and ureteroscopy (URS) cannot reach ureteral level of stone were excluded. We used semirigid URS (Wolf) 6/7.5F, monitor video, and holmium laser: YAG litotriptor (Versa Pulse, Lumenis, Germany), with wavelength 2100 nm, output 1-60 watt, fiber length 365 μm, laser power 2.5-10 watt with energy 0.5-1 Joule/5-15 Hz. Results: Of 50 ureteral stone patients, consisted proximal 13 (26%) and distal 37 (74%) were included in this study. Mean age 42.94 ± 11.31 years, with 28 male (56%) and 22 female (44%). Mean stone burden was 88.10 ± 57.41 mm2. There were 6 (12%) patients with multiple stones. This procedure consumed energy 1079.02 ± 1624.00 joule and duration of operation was 19.02 ± 21.17 minutes. We inserted DJ stent after the procedure in 41 patients (82%). There were 2 failure (4%), which were stone migration to kidney and conversion to open surgery. There were significant differences of stone burden (p 0.013), duration of operation (p 0.038), and stone number (p 0.000) with stone free rate, but not in age, sex, stone location and energy. Stone free rate of this procedure was 90%. Conclusion: Stone burden, duration of operation, and stone number were predictive factors for success of holmium laser: YAG lithotripsy in ureteral calculi management.